Chlorine Tolerance and Cross-Resistance to Antibiotics in Poultry-Associated Salmonella Isolates in China - Xiao, Xingning; Bai, Li; Wang, Sheng; Liu, Lisha; Qu, Xiaoyun; Zhang, Jianmin; Xiao, Yingping; Tang, Biao; Li, Yanbin; Yang, Hua; Wang, Wen (Frontiers in Microbiology, 2022)
Chlorine disinfectants have been widely used in the poultry supply chain but this exposure can also result in the development of bacterial tolerance to chlorine and this is often linked to antibiotic cross-resistance. The objectives of this study were to investigate sodium hypochlorite (NaClO) tolerance of Salmonella isolated from poultry supply chains and evaluate cross-resistance. We collected 172 Salmonella isolates from poultry farms, slaughter houses and retail markets in China during 2019-2020. We found that S. Enteritidis, S. Kentucky, and S. Typhimurium constituted > 80% of our Salmonella isolates. Overall, 68% of Salmonella isolates were resistant to > 3 antibiotics and S. Kentucky displayed a significantly (p > 0.05) higher frequency (93.2%) of multidrug resistance than the other serovars. Tolerance to chlorine at MIC > 256 mg/L was detected in 93.6% of isolates (161/172) and tolerant isolates displayed higher decimal reduction times (D value) and less ultrastructural damage than did the suspectable strains under chlorine stress. Spearman analysis indicated significant positive correlations between chlorine tolerance (evaluated by the OD method) and antibiotic resistance (p < 0.05) to ceftiofur, tetracycline, ciprofloxacin and florfenicol and this was most likely due to efflux pump over-expression. The most frequently detected chlorine resistance gene was qacEΔ1 (83.1%, n = 143) and we found a positive correlation between its presence and MIC levels (r = 0.66, p < 0.0001). Besides, we found weak correlations between chlorine-tolerance and antibiotic resistance genes. Our study indicated that chlorine disinfectants most likely played an important role in the emergence of chlorine tolerance and spread of antibiotic resistance and therefore does not completely control the risk of food-borne disease. The issue of disinfectant resistance should be examined in more detail at the level of the poultry production chain.